Factors influencing the use of direct oral anticoagulants among patients with chronic chagas cardiomyopathy - Gómez-Ochoa, Sergio Alejandro (2024)
Objective. Chronic Chagas cardiomyopathy (CCC) carries a high risk of embolic events due to structural changes in the left ventricle and frequent conduction disorders. However, there is limited data on anticoagulant prescription patterns and factors influencing the use of direct oral anticoagulants (DOACs) in these patients. This study aims to characterize CCC patients based on the anticoagulant therapy received and identify factors associated with DOACs use. Materials and Methods. A cross-sectional study was conducted at a tertiary-level hospital in Colombia between 2019-2022. Multivariate logistic regression models were used to assess factors associated with anticoagulant therapy and DOACs use. Results. Among 224 CCC patients, 65.7% (n=153) were on anticoagulants, with DOACs being the most prescribed (53%). Notably, 35% of patients at high risk of stroke (CHA2DS2-VASc) were not receiving anticoagulants. Atrial fibrillation (OR 256.08; 95% CI 61.94-1058.72), ventricular aneurysms (OR 4.82; 95% CI 1.54-15.09), and reduced interventricular septal thickness (OR 0.75; 95% CI 0.60-0.92) were associated with anticoagulant use. DOACs were mainly prescribed for patients with atrial fibrillation (OR 13.29; 95% CI 2.47-71.56) and high bleeding risk (HAS-BLED ≥3, OR 11.36; 95% CI 1.15-112.11). Conclusions. A significant proportion of CCC patients were not receiving anticoagulants despite their high risk of stroke and embolic events. The use of anticoagulation was significantly associated with atrial fibrillation, the presence of ventricular aneurysms and reduced interventricular septal thickness. It is crucial to raise awareness among healthcare professionals in endemic areas to improve treatment.